Expressing Four Humour Techniques in Gus Miftah's Dakwahtainment Activities on YouTube - Akhmad Nasir; Iswandi Syahputra; Hamdan Daulay (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
Studies on humor in dakwahtainment have largely focused on its rhetorical function in attracting audiences or explaining laughter through the perspectives of Superiority Theory, Incongruity Theory, and Benign Violation Theory. These perspectives, however, have paid limited attention to how humor is constructed as a communication strategy within contemporary digital preaching. This study aims to examine the forms of humor employed by Gus Miftah and to explain the mechanisms through which such humor is constructed using Arthur Asa Berger's humor techniques framework. The study adopted a qualitative approach using a qualitative content analysis design. The data consisted of seven YouTube sermons delivered by Gus Miftah, which were purposively selected based on the intensity of humorous content, the diversity of preaching themes, and the representation of his communication style. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while interpretation was guided by Arthur Asa Berger's humor framework, which classifies humor into the dimensions of logic, identity, language, and action. The findings reveal four dominant forms of humor: fictional storytelling in preaching, laughable misfortune, surprising twists, and joking through swearing. These forms demonstrate that humor is constructed through the combination of multiple communication techniques that manage audience expectations, foster social closeness, and sustain audience engagement in the delivery of religious messages. This study contributes to the literature on dakwahtainment by repositioning humor not merely as a rhetorical style or a trigger of laughter, but as a systematically constructed communication strategy within contemporary digital preaching.